Rb-Sr, Sm-Nd and Ar-Ar isotopic systematics of Antarctic nakhlite Yamato 000593 - Misawa,Keiji; Shih,Chi-Yu; Wiesmann,Henry; Garrison,Daniel H.; Nyquist,Laurence E.; Bogard,Donald D. (National Institute of Polar Research, 2005)
P(論文) sotopic analysis of the newly found Antarctic nakhlite Yamato (Y) 000593 yields a Rb-Sr age of 1.30±0.02Ga with an initial ^(87)Sr/^(86)Sr of 0.702525±0.000027, a Sm-Nd age of 1.31±0.03Ga with an initial ε_(Nd) of + 16.0±0.2 and an Ar-Ar isochron age of <=1.36Ga. The concordancy of these three ages and Rb-Sr and Sm-Nd initial isotopic signatures strongly suggest that Y000593 crystallized from low Rb/Sr, light REE-depleted source materials ～1.31Ga ago. The crystallization age of Y000593 is compared with the age data of non-Antarctic nakhlites (Nakhla, Governador Valadares, Lafayette and Northwest Africa 998) and Chassigny. The initial Sr and Nd isotopic signatures suggest that Lafayette and Y000593 were co-magmatic or at least came from very similar magmas. Cosmogenic ^(36)Ar concentrations in Y000593 resemble those in other nakhlites. The similarities in crystallization and ejection ages and in petrologic features suggest the nakhlites were derived from similar source regions, and launch pairing of nakhlites and Chassigny. The Rb-Sr data for Y000593 show that the isotopic system is disturbed by pre-terrestrial alteration of olivine. Although many of the acid-leached residues of mineral fractions fall along the 1.30Ga Rb-Sr isochron, leached olivine does not. This indicates the lack of isotopic equilibrium between the olivine fractions and the secondary alteration phases. A tie-line between two olivine leachates provides a calculated "age" of 650±80Ma with an initial ^(87)Sr/^(86)Sr of ～0.70465, which gives a hint for the isotopic signatures of local brine as well as the timing of an aqueous alteration event on the Martian surface. departmental bulletin paper